Diagnostic Challenges of Weil’s Disease with Acute Kidney Injury: A Case Report and Clinical Review - Made Priska Arya Agustini; Putu Itta Sandi lesmana Dewi; I Dewa Ayu Made Dian Lestari; I Wayan Sunaka (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2025)
Background: Severe leptospirosis or Weil’s disease can cause multi-organ failure, which is characterized by jaundice and acute kidney injury in approximately 10% of cases. Its nonspecific symptoms often lead to misdiagnosis with other acute febrile illnesses, resulting in delayed diagnosis. Case Presentation: A 48-year-old male construction worker presented with fever, headache, myalgia, epigastric pain, nausea, and vomiting for four days without any signs of bleeding. The patient lived and worked at a project site adjacent to rice fields. Physical examination revealed fever, icteric sclera, conjunctival suffusion, and tenderness of the gastrocnemius muscle. Laboratory tests showed leukocytosis, thrombocytopenia, impaired renal function, elevated liver enzymes, hyponatremia, and hypokalemia. The patient was diagnosed with Weill’s disease. He was treated with antibiotics and supportive therapy. Sixteen days after discharge, the patient reported gradual improvement and had resumed normal activities. Discussion: Patients presenting with acute febrile illness should undergo a comprehensive evaluation, and leptospirosis should be considered when leukocytosis, neutrophilia, and thrombocytopenia are observed in a complete blood count. A detailed history focusing on risk factors and associated symptoms, along with additional diagnostic tests based on the criteria, can help guide the diagnosis. Antibiotic therapy should be initiated immediately in patients with suspected or probable leptospirosis without waiting for serological confirmation. Conclusion: This case highlights the diagnostic challenges of leptospirosis, particularly in resource-limited healthcare settings. Enhancing clinical awareness, improving access to rapid diagnostic tools, and optimizing preventive measures are crucial to reducing morbidity and mortality rates